2019
DOI: 10.1080/15459624.2018.1536826
|View full text |Cite
|
Sign up to set email alerts
|

A field evaluation of a single sampler for respirable and inhalable indium and dust measurements at an indium-tin oxide manufacturing facility

Abstract: Indium-tin oxide production has increased greatly in the last 20 years subsequent to increased global demand for touch screens and photovoltaics. Previous studies used measurements of indium in blood as an indicator of indium exposure and observed associations with adverse respiratory outcomes. However, correlations between measurements of blood indium and airborne respirable indium are inconsistent, in part because of the long half-life of indium in blood, but also because respirable indium measurements do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…A large-scale study in Korea previously estimated the fraction of respirable indium dust ( n = 13) from the total dust ( n = 16) at 39% [ 14 ]. A comparable Japanese study revealed the mean respirable fraction in the indium manufacturing process ( n = 17) to be 38% (Total In/Respirable In 2.64) [ 15 ], and a similar study in the US revealed a mean respirable indium fraction of 30% (respirable In: 10.9 µg/m 3 ; inhalable In: 36.5 µg/m 3 ) [ 16 ], consistent with the results of this study. In contrast, in the indium-recycling plant, the proportion of respiratory indium dust was low [ 17 ].…”
Section: Discussionsupporting
confidence: 88%
“…A large-scale study in Korea previously estimated the fraction of respirable indium dust ( n = 13) from the total dust ( n = 16) at 39% [ 14 ]. A comparable Japanese study revealed the mean respirable fraction in the indium manufacturing process ( n = 17) to be 38% (Total In/Respirable In 2.64) [ 15 ], and a similar study in the US revealed a mean respirable indium fraction of 30% (respirable In: 10.9 µg/m 3 ; inhalable In: 36.5 µg/m 3 ) [ 16 ], consistent with the results of this study. In contrast, in the indium-recycling plant, the proportion of respiratory indium dust was low [ 17 ].…”
Section: Discussionsupporting
confidence: 88%
“…The Button (inhalable) sampler was studied on five occasions (5 studies; 23%) followed by the Respicon sampler (4 studies; 18%), which is capable of measuring multiple aerosol fractions. In some studies, the samplers have been referred to as different sample names, for example the IOM head with the PU foam [ 28 ] is also referred to as the IOM dual sampler [ 29 ]. In this instance this is referred to as the IOM dual sampler hereafter.…”
Section: Resultsmentioning
confidence: 99%
“…Under half of the retrieved studies assessed the respirable fraction (32%). This includes the Higgins-Dewell cyclone [ 37 , 38 ], the Aluminium SKC cyclone [ 39 , 40 ], and the GK2.69 cyclone [ 29 ]. The thoracic fraction has only been assessed in two of the retrieved studies (>9%), with the GK2.69 cyclone being used in both [ 38 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations